Cancer Immunotherapy: The Potential of Adoptive T cell Therapy for Cancer - Tawinwung, Supannikar (Journal of Basic and Applied Pharmacology, 2017)
The immune system evolved to distinguish and eliminate malignant cells during the initial transformation. However, cancer cells manage to invade immune recognition and destruction, resulting in a persistent cancer. Recently, global cancer research has focused on immunotherapy, the approach to treat cancer by augmenting the immune system against it. This approach aims to stimulate immune cells to specifically recognize and destroy target cancer without affecting normal tissues. The current immunotherapeutic strategies include cancer vaccines, oncolytic viruses, checkpoint inhibitors and, adoptive cell therapy. The present article describes the function of tumor immunity and main strategies in cancer immunotherapy with a particular emphasis on advances and clinical benefits of adoptive T cell therapy.